Analysis of Needs for Inquiry-Based Model Development Integrated Project Assignments in High School Chemistry Teaching - Kiki Ledya; Manihar Situmorang; Ramlan Silaban (Universitas Serambi Mekkah, 2024)
The aim of the research is to determine the analysis of student and teacher needs in developing an inquiry-based model integrated with project assignments in high school (SMA) chemistry teaching. The research method is qualitative and quantitative with the research subjects being class XII students majoring in science in the city of Lhokseumawe, Aceh Province. The instruments used in this research were questionnaires, observation sheets and interviews. Several needs analysis data were obtained that support learning media and teachers' tendencies to use the inquiry learning model. Survey data was obtained from students and teachers as follows which shows that the needs of students are (1) students find it difficult to understand chemistry material 62.5%, (2) students feel happy if teachers use models in learning 70%, (3) students want real (contextual) learning 90%. The data also shows that the needs needed by teachers are (1) teachers understand the use of the 100% learning model, (2) teachers often use the 60% inquiry model, (3) teachers experience difficulties in implementing the 80% inquiry model. data on the use of the inquiry model by teachers shows (1) teachers are familiar with the use of the inquiry model 60%, (2) teachers have applied the inquiry model in class 95%, (3) teachers experience difficulties in carrying out learning using the inquiry model 80%. The conclusion of the needs analysis through a survey of students and teachers for the development of an inquiry-based model integrated with project assignments on teaching materials or active learning resources that can be connected to the real world (contextual) was that the percentage of student needs was 95% and the percentage of teacher needs was 89%.